Exploring the Relationship Using Mosston and Ashworths Teaching Styles of Physical Education Teachers in Turkey - SEVILMIS, Ali; YILDIZ, Ozer (Asian Journal of Contemporary Education, 2021)
In this study, the relationship using Mosston and Ashworth’s teaching styles of physical education teachers and their using intensities regarding stills were examined according to their gender, experience, and serving in public and private schools. In collecting, analyzing, and interpreting the study data, a qualitative study paradigm was utilized. In the scope of study, semi-structured interview was made with 23 physical education teachers selected by purposeful sampling. According to the result of data analysis, while physical education teachers were taught lessons, it was revealed that they teaching-centered teaching styles. In addition, when the teaching styles of physical education teachers are evaluated in the context of intercode relationships, it was revealed that they used the most frequently the styles related to “Command-A – Reciprocal-C” “Command-A – Practice-B”. Intercode relationships decreases from teaching-centered teaching styles to learning-centered teaching styles. Especially, it was revealed that “Self-Teaching- K” and “Convergent and Divergent Discovery- G/H” styles, among learning-centered teaching styles, were not related to the other styles at all. Teaching styles teachers use is an indicator of that teaching-centered education are more prominently given. In addition, the intensities using Mosston and Ashworth’s teaching styles of the teachers according to the gender, experience, serving in the public and private schools were identified.